RESEARCH ON THE PERSONAL INCOME TAX APPLICATION TO WAGES IN THE BALTIC STATES - Puzule, Anita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Personal income tax and social insurance contributions must be paid on wages into the budget, the revenue of which most directly affects the changes in the number of persons engaged in the national economy and the increase of the average wage. To be able to evaluate how favourable the personal income tax systems applicable to employees are in the Baltic States, the author compares the factors that affect taxation and the tax burden in Latvia, Lithuania and Estonia, which have experienced tax reforms in the recent years. The aim of the research is to perform a comparative study of the requirements and issues of personal income tax application to wages in Latvia, Lithuania, and Estonia. The monographic, comparative and analytical analysis, logical construction, and grouping methods have been used in the research study. Based on the research study, the author has concluded that despite the similarities in the personal income tax systems, each Baltic state has different normative regulation. The tax burden on Estonian taxpayers relative to wages is lower than that in Lithuania and Latvia.